Dynamic behaviour of direct spring loaded pressure relief valves connected to inlet piping: IV review and recommendations. (July 2017) - Hős, C.J.; Champneys, A.R.; Paul, K.; McNeely, M.
Abstract: Recent progress by a number of different groups and authors is reviewed on the stability properties of direct-spring pressure relief valves connected to pressure vessels with or without piping systems. Various different notions of stability and mechanisms for instability are revealed both in the case of gas and liquid service. It is stressed that it is not the valve itself that is stable or unstable, rather the harmful vibrations arise through interactions between the valve and its surroundings — the inlet piping, the reservoir, and any outlet piping. A distinction is drawn between underlying instability mechanisms and how these may be triggered during transient operations. The purpose of the work is to provide a coherent simplified account that will be of practical use for proposing new operational guidelines and mitigation strategies. Among these various mechanisms, oscillatory instability due to the interaction with aquarter-wave acoustic mode in the inlet piping is argued to be the most important to mitigate. Highlights: A synthesis of recent work on PRV systems leads to a complete survey of instability mechanisms and their prediction. It is not accurate to refer to a particular valve as being stable or unstable. It is the system — valve, reservoir, piping, fluid and operating conditions — that may or may not develop an instability. It is important to distinguish between fundamental instabilities and triggering mechanisms causing a particular event. We have identified indicates five types of fundamental instability, and simple design formulae for preventing them. Of all these mechanisms, it would appear that the quarter-wave in-stability is by far the most common and dangerous.